The Tenth International Workshop on MULTIFREQUENCY BEHAVIOUR OF HIGH ENERGY COSMIC SOURCES Palermo, Italy, 2013 - Editorial, Foreword (Acta Polytechnica CTU Proceedings, 2014)
Organizing Institutions: Istituto di Astrofisica e Planetologia Spaziali IAPS-INAF, Roma, Italy Dpt de Cargas Utiles y Ciencias del Espacio, DCUCE-INTA Madrid, Spain E.O. Hulburt Center for Space Research, HCA-NRL, Washington D.C., USA Max-Planck Institut fr Extraterrestrische Physik, MPE, Garching, Germany St. John’s College, SJC, Annapolis MD, USA Institute für Astronomie und Astrophysik, Karls Eberhard, Universität SAND 1, Tübingen, Germany ASCR - Astronomical Institute, Ondřejov, Czech Republic CTU - Czech Technical University, Prague, Czech Republic